(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2019)
The General Law on the Rights of Persons with Disabilities and their social inclusion of 2013 in its article 12.3.a) speaks for the first time of the capacity report in the process of recognition of the degree of disability. The Community of Madrid Base Centers has been carrying out this opinion for a few years and not only focuses on the limitations and also collects the capacities and strengths of the people who serve, in line with the United Nations Convention on the Rights of Persons with Disabilities in 2006. This article analyzes this experience to conclude that this tool can be very interesting to achieve a better job orientation of people with disabilities and facilitate accessibility and adaptation of jobs and, therefore, should be generalized its use.